Anode performance of hydrothermally grown carbon nanostructures and their molybdenum chalcogenides for Li-ion batteries. (3rd May 2018) - Simsir, Hamza; Eltugral, Nurettin; Frohnhoven, Robert; Ludwig, Tim; Gönüllü, Yakup; Karagoz, Selhan; Mathur, Sanjay
Abstract: Abstract : Three different hydrothermally grown carbonaceous materials and their molybdenum chalcogenides derived from glucose (HTC, HTC–MoO2, HTC–MoS2 ) were investigated to evaluate their potential as Li-ion battery anodes. All tested materials exhibited good cycling performance at a current density of 100 mA/g and showed high coulombic efficiency, >98%, after the 50th cycle. Reversible charge capacities of HTC, HTC–MoO2, and HTC–MoS2 were 296, 266, and 484 mAh/g, respectively, after 50 successive cycles. This study demonstrated that the HTC–MoS2 showed the highest reversible charge capacity which promises to be a good candidate for an environmentally friendly anode material for Li-ion batteries.